2013
DOI: 10.1016/j.bmc.2013.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-methylumbelliferyl α-d-mannopyranosyl-(1→6)-β-d-mannopyranoside and development of a coupled fluorescent assay for GH125 exo-α-1,6-mannosidases

Abstract: Certain bacterial pathogens possess a repertoire of carbohydrate processing enzymes that process host N-linked glycans and many of these enzymes are required for full virulence of harmful human pathogens such as Clostridium perfringens and Streptococcus pneumoniae. One bacterial carbohydrate processing enzyme that has been studied is the pneumococcal virulence factor SpGH125 from S. pneumoniae and its homologue, CpGH125, from C. perfringens. These exo-α-1,6-mannosidases from glycoside hydrolase family 125 show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…When the same procedure was applied to 2 : 3,4 : 6‐di‐ isopropylidene‐protected mannose 10 , the β‐mannopyranoside 7β was formed almost exclusively in yields over 80 %. Our results with diisopropylidene mannose 10 are related to literature reports, where 10 was reacted under similar Mitsunobu conditions with phenol12 or with 4‐methylumbelliferone,13 mainly providing the respective β‐ D ‐mannosides in equally pleasant yields. Thus, the reducing mannose derivative 10 can be regarded as an excellent starting material for the Mitsunobu synthesis of β‐ D ‐mannosides.…”
Section: Methodssupporting
confidence: 87%
“…When the same procedure was applied to 2 : 3,4 : 6‐di‐ isopropylidene‐protected mannose 10 , the β‐mannopyranoside 7β was formed almost exclusively in yields over 80 %. Our results with diisopropylidene mannose 10 are related to literature reports, where 10 was reacted under similar Mitsunobu conditions with phenol12 or with 4‐methylumbelliferone,13 mainly providing the respective β‐ D ‐mannosides in equally pleasant yields. Thus, the reducing mannose derivative 10 can be regarded as an excellent starting material for the Mitsunobu synthesis of β‐ D ‐mannosides.…”
Section: Methodssupporting
confidence: 87%
“…This stereo-differentiating effect of isopropylidene protecting groups was also observed in other cases with D-mannopyranose [ 46 , 61 ]. It might be used as a key to a reliable approach to otherwise difficult to synthesize β-mannosides using the Mitsunobu procedure.…”
Section: Reviewsupporting
confidence: 73%
“…Previous work has identified three subsites, −1, +1 and +2, in CpGH125 through a complex with 1,6-α-mannotriose (PDB ID: 5M7Y), 19 and studies of a di-saccharide substrate that binds in the −1/+1 subsites revealed saturation kinetics, whereas a monosaccharide substrate, 2,4dinitrophenyl α-mannoside (DNPMan), that bound only in the −1 subsite did not. 18,26 Previous poor electron density in the +2 subsite suggests that this may represent the low affinity binding site, a conclusion supported by subsequent X-ray crystallographic studies (vide infra). The two tighter affinities therefore should likely reflect binding at the −1 and +1 subsites; however, we cannot draw conclusions as to which value is assigned to each of these subsites.…”
Section: Resultsmentioning
confidence: 82%
“…1,2 Mannosidases and mannanases catalyze the hydrolysis of mannoside linkages and these enzymes are found within 11 GH families. Enzymes within families GH2, 5,26,38,76,92,99,113,125 and 134 perform catalysis through itineraries along the O S 2 -B 2,5 -1 S 5 region of conformational space whereas enzymes of families GH47 and 134 react through the 3 S 1 -3 H 4 -1 C 4 conformational axis (Fig. 1b).…”
mentioning
confidence: 99%